(untitled) (International Association of Biologicals and Computational Digest, 2022)
Synthetic pyrethroids are insecticide as well as pesticide made from naturally occurring pyrethrins found in dried Chrysanthemum flowers’ pyrethrum. In present review use of pyrethroid as insecticide and its harmful effects on human beings are focused. Pyrethroids Modifying the kinetics of voltage-sensitive sodium channels, which mediate the nerve membrane’s temporary increase in sodium permeability that underpins the nerve action potential, has an effect on insect nerves, with is benefits it also shows adverse effect on human health if its consumption is high it can cause damage to sperm DNA, respiratory disorder, circulatory disease and many more.